SHRIMP U–Pb and Ar–Ar geochronology of major porphyry and skarn Cu deposits in the Balkhash Metallogenic Belt, Central Asia, and geological implications - Chen, Xuanhua; Seitmuratova, Eleonora; Wang, Zhihong; Chen, Zhengle; Han, Shuqin; Li, Yong; Yang, Yi; Ye, Baoying; Shi, Wei (Journal of Asian earth sciences, 2014)
•We newly studied major porphyry and skarn Cu deposits in the Balkhash Metallogenic Belt, Central Asia.•The thermal histories from magma intrusion and cooling for the deposits are given based on geochronology.•The metallogenic ages of the deposits are constrained by the thermal histories.•Metallogenic series in the Balkhash Metallogenic Belt and adjacent areas is discussed.•The Balkhash Metallogenic Belt is correlated to the Junggar metallogenic belt. The Balkhash Metallogenic Belt (BMB) in Kazakhstan, Central Asia, with the occurrence of the super-large Kounrad and Aktogai, the large Borly porphyry Cu–Mo deposits, and the large Sayak skarn polymetallic ore-field, is one of the central regions of the Paleozoic Central Asian metallogenic domain and orogenic belt. In this study, newly obtained SHRIMP zircon U–Pb ages of nine samples and 40Ar/39Ar ages of six mineral samples (inclding hornblende, biotite and K-feldspar) give more detailed constraints on the timing of the granitic intrusions and their metallogeny. Porphyritic monzonite granite and tonalite porphyry from the Kounrad deposit yield U–Pb zircon SHRIMP ages of 327.3±2.1Ma and 308.7±2.2Ma, respectively. Quartz diorite and porphyritic granodiorite from the Aktogai deposit yield U–Pb SHRIMP ages of 335.7±1.3Ma and 327.5±1.9Ma, respectively. Porphyritic granodiorite and granodiorite from the Borly deposit yield U–Pb SHRIMP ages of 316.3±0.8Ma and 305±3Ma, respectively. Diorite, granodiorite, and monzonite from the Sayak ore-field yield U–Pb SHRIMP ages of 335±2Ma, 308±10Ma, and 297±3Ma, respectively. Hornblende, biotite, and K-feldspar from the Aktogai deposit yield 40Ar/39Ar cooling ages of 310.6Ma, 271.5Ma, and 274.9Ma, respectively. Hornblende, biotite, and K-feldspar from the Sayak ore-field yield 40Ar/39Ar cooling ages of 287.3±2.8Ma, 307.9±1.8Ma, and 249.8±1.6Ma, respectively. The new ages constrain the timing of Late Paleozoic felsic magmatism to ∼336 to ∼297Ma. Skarn mineralization in the Sayak ore-field formed at ∼335 and ∼308Ma. Porphyry Cu–Mo mineralization in the Kounrad deposit and the Aktogai deposit formed at ∼327Ma, and in the Borly deposit at ∼316Ma. The Late Paleozoic regional cooling in the temperature range of ∼600°C to ∼150°C occurred from ∼307 to ∼257Ma.